Visions and revisions : higher education in Bangladesh 1947-1992 - Siddiqui, Zillur Rahman (Dhaka : The University Press Limited, 1997)
Social Science
Includes index and bibliographical references
2000-06-25
Keywords: Higher education; Vision; Bnagladesh